(untitled) (Open Academia: Journal of Scholarly Research, 2024)
This article delves into the complex connection between joy and sadness, two essential human emotions. It investigates how these emotions coexist and interact, their temporary nature, and their capacity to facilitate personal development. Furthermore, it analyzes the attributes and impacts of joy and sadness on individuals and their interactions within society